The process of change in the treatment of personality disorder in a forensic inpatient setting - Willmot, Phil (2016)
This thesis explores the question, what are the important change processes in the treatment of personality disorder in a male forensic inpatient setting? A number of empirically supported therapies for personality disorder stress the importance of the therapist-client relationship in the change process. Therapist-patient relationships are therefore an important focus in this thesis. However, given the lack of research into change processes in this population, the focus is not limited to the therapist-patient relationship, but also considers other relationships and other aspects of the treatment milieu. A model of change processes for this patient group is developed through a series of studies.